Trend Analysis on 13 Years of Halal Research; Investigation on Halal Food Research - Risyawati Mohamed Ismail; Mastora Mustafar; Noorulsadiqin Azbiya Yaacob; Fadhilah Mat Yamin (International Journal of Supply Chain Management, 2020)
Despite all the attention halal received from the economic point of view, the academic exploration of the subject has yet to be analyzed. Research on the different aspects of halal has begun, but due to the broad scope of the subject, no one has yet studied the overall approach and trend of research on halal. While the subject area is becoming popular with stakeholders, it is interesting to see whether the academic community is keeping up with the booming growth of the industry. Published articles from 2005 to the beginning of 2019 were used in this study. In this study, 13 years of 'halal' publications in the fields of social sciences, art humanities and business management were extracted, analyzed and interpreted in two major databases in order to understand the actual situation of halal research carried out since the year 2005. Findings showed that most halal research conducted over the last 13 years focuses more on halal product and halal food, and focuses mainly on consumer behavior and outlook, halal slaughter, halal meat and food production, to name a few. Such results indicated that there are still numerous halal sub-topics that researchers need to investigate, and that the body of knowledge itself needs rigorous research in the future.